2015
DOI: 10.1021/acscatal.5b01348
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermal Stability and Methane-Oxidation Activity of Pd/Al2O3 Catalysts by Atomic Layer Deposition of ZrO2

Abstract: The effect of modifying Pd/Al2O3 catalysts by atomic layer deposition of 1 nm ZrO2 films was studied. For deposition on oxidized, PdO/Al2O3 catalysts, TEM imaging, EDS mapping, and metal-dispersion measurements confirmed the presence of the thin ZrO2 over both the Al2O3 support and the metal particles. The ZrO2 films were surprisingly stable, forming a well-crystallized phase only above 1173 K. The ZrO2 coating over the PdO particles created a semicore–shell-like structure that stabilized the metal against sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 28 publications
(63 reference statements)
3
85
1
Order By: Relevance
“…The deposition of 20 ALD cycles of either CeO 2 or ZrO 2 , with calcination at 773 K, did not change the patterns. While peaks associated with crystalline CeO 2 would be difficult to distinguish from the mixture of tetragonal and monoclinic ZrO 2 , previous work has shown that ALD films this thin (the film on the 20 CeO 2 /ZrO 2 sample is only 0.33 nm thick) are invisible to XRD [20]. The effects of calcining the same three samples to 1073 K is shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 90%
“…The deposition of 20 ALD cycles of either CeO 2 or ZrO 2 , with calcination at 773 K, did not change the patterns. While peaks associated with crystalline CeO 2 would be difficult to distinguish from the mixture of tetragonal and monoclinic ZrO 2 , previous work has shown that ALD films this thin (the film on the 20 CeO 2 /ZrO 2 sample is only 0.33 nm thick) are invisible to XRD [20]. The effects of calcining the same three samples to 1073 K is shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 90%
“…The term "static" is used here to refer to the sample inside the reactor being exposed to non-flowing (i.e., static) precursors. The reactor itself can be rotating, or the particles inside the reactor can be agitated in various other ways [44,66,67], although simple static reactors without any moving parts have successfully been used to coat catalysts and SOFC electrodes [68][69][70][71][72][73][74][75]. In a static reactor, the sample is held in a sealed vessel that can be evacuated.…”
Section: Ald Reactor Designs For Catalysts and Sofc Electrodesmentioning
confidence: 99%
“…However, since only a few ALD cycles are required to reach substantial weight loadings (see Section 1.4), long exposure and purge times (on the order of 10's of minutes or perhaps even hours) may be acceptable, as demonstrated by the fixed bed static reactor design developed by researchers at BASF [56]. It should be noted that exposure times can be shortened by using agitated or rotating bed reactors [44,66,67], using thin pelletized samples (Figure 3) [70][71][72][73], and increasing precursor partial pressures [56,57].…”
Section: Ald Reactor Designs For Catalysts and Sofc Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the catalytic activity is not stable when directly used in the reactions. Therefore, impregnation and embedding of the Pd-based catalysts in metal oxide support are required to increase the activity and stability of the active Pd-based catalysts [10,27]. Herein, an attempt to investigate the influences of different precursors used for preparation of ceria materials by thermal decomposition of metal complexes on the function as the catalytic support materials has been accomplished.…”
Section: Introductionmentioning
confidence: 99%